Clinical evaluation of diabetic neuropathy in adult patients with type 1 diabetes and its possible association with insulin resistance - González-Milán, Claudia; Ramírez-Rentería, Claudia; Molina-Ayala, Mario; Ferreira-Hermosillo, Aldo (Revista Médica del Instituto Mexicano del Seguro Social, 2018)
Background: In Mexico, there is a lack of information regarding the prevalence and characteristics of Diabetic Neuropathy (DN) in patients with type 1 diabetes (T1D). Although it was, considered as a country with low-incidence of T1D, recent publications show that T1D frequency is under-represented. The aim of this paper is to describe the frequency and severity of DN in patients with T1D using a clinical scale and assess its possible association with insulin resistance.Methods: We evaluated 48 patients from T1D Clinic. We assessed clinical and biochemical characteristics and determined insulin resistance through estimated glucose dispose rate (eGDR). Patients underwent a neurologic evaluation using a previously validated score.Results: Seventy-three percent of patients had DN (54% mild and 19% moderate neuropathy). Twenty-nine percent of total population had Metabolic Syndrome. Major predictor factors for DN were the presence of diabetes for more than 13 years (OR 4.6, CI95%: 1.09-15.7), achieving treatment goals during the first 5 years (OR 0.22, CI95%: 0.05-0.87) and eGDR > 7.32 mg/kg/min (OR 0.096, CI95%: 0.011-0.81).Conclusions: The clinical scale performed in this study is a useful screening tool for DN in adults with long-standing T1D. DN is more frequent in patients with longer evolution of diabetes and poor glucose control during the initial years after diagnosis as expected, but insulin resistance should also be considered as an additional risk factor in this group.